Analysis of genetic distance between Peruvian Alpaca (Vicugna Pacos) showing two distinct fleece phenotypes, Suri and Huacaya, by means of microsatellite markers - La Manna, Vincenzo (2016)
Two coat phenotypes exist in Alpaca, Huacaya and Suri. The two coats show different fleece structure, textile characteristics and prices on the market. Although present scientific knowledge suggests a simple genetic model of inheritance, there is a tendency to manage and consider the two phenotypes as two different breeds. A 13 microsatellite panel was used in this study to assess genetic distance between Suri and Huacaya alpacas in a sample of non-related animals from two phenotypically pure flocks at the Illpa-Puno experimental station in Quimsachata, Peru. The animals are part of a germplasm established approximately 20 years ago and have been bred separately according to their coat type since then. Genetic variability parameters were also calculated. The data were statistically analyzed using the software Genalex 6.3, Phylip 3.69 and Fstat 2.9.3.2. The sample was tested for Hardy-Weinberg equilibrium (HWE) and after strict Bonferroni correction only one locus (LCA37) showed deviation from equilibrium (P<0.05). Linkage disequilibrium (LD) was also tested and 9 loci associations showed significant disequilibrium. Observed heterozygosis (Ho= 0.766; SE=0.044), expected heterozygosis (He=0.769; SE=0.033), number of alleles (Na=9.667, SE=0.772) and Fixation index (F=0.004; SE=0.036) are comparable to data from previous studies. Measures of genetic distance were 0.06 for Nei’s and 0.03 for Cavalli-Sforza’s. The analysis of molecular variance reported no existing variance between populations. Considering the origin of the animals, their post domestication evolution and the reproductive practices in place, the results do not show genetic differentiation between the two populations for the studied loci.